Diallel analysis and inbreeding depression in agronomic and technological traits of cotton genotypes - Rodrigues, Josiane Isabela da Silva; Bhering, Leonardo Lopes; Farias, Francisco José Correia; Teodoro, Paulo Eduardo; Carvalho, Luiz Paulo de (Bragantia, 2018)
Cotton provides about 90% of the world textile fiber, and is one of the crops of greater industrial relevance. The objectives of this study were to estimate the inbreeding depressionand the genetic effects involved in the control of the agronomic andfiber quality traits in F1 and F2 generations and to identify promising hybrids for obtaining superior cotton genotypes. Two cultivars of upland cotton and two moco (Brazilian endemic) cotton were crossed using a half-diallel scheme. The following traits were evaluated: percentage of fibers and weight of one boll, fiber length, fiber uniformity, short fiber index, fiber strength, and micronaire index. The additive genetic effects are predominant in the evaluated agronomic and fiber quality traits. Cultivar FM 966 is the most suitable parent to compose crossing blocks for the improvement of cotton agronomic and fiber quality traits. The hybrids FM 966 × CNPA 7MH and FM 966 × BRS 286 are the most promising for obtaining segregating populations aiming to select superior genotypes. Inbreeding depression is more pronounced in the agronomic traits than in the fiber quality traits.
Keywords: Gossypium hirsutum L. r. latifolium Hutch; Gossypium hirsutum L. r. marie galante Hutch; Combining ability; Parents selection